2019
DOI: 10.1103/physrevb.100.134424
|View full text |Cite
|
Sign up to set email alerts
|

Universality of annihilation barriers of large magnetic skyrmions in chiral and frustrated magnets

Abstract: Magnetic skyrmions are whirls in the magnetization whose topological winding number promises stability against thermal fluctuations and defects. They can only decay via singular spin configurations. We analyze the corresponding energy barriers of skyrmions in a magnetic monolayer for two distinct stabilization mechanisms, i.e., Dzyaloshinskii-Moriya interaction (DMI) and competing interactions. Based on our numerically calculated collapse paths on an atomic lattice, we derive analytic expressions for the saddl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 55 publications
6
24
0
Order By: Relevance
“…22 occurs. The chimera skyrmion collapse and the radial antiskyrmion collapse are similar to that found in simulations neglecting HOI 16,22,50 .…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…22 occurs. The chimera skyrmion collapse and the radial antiskyrmion collapse are similar to that found in simulations neglecting HOI 16,22,50 .…”
Section: Resultssupporting
confidence: 80%
“…3j, k which show the spin structures in the vicinity of the saddle point of the two types of annihilation mechanisms). Interestingly, the chimera collapse mechanism has been previously discussed in ultrathin films with very strong exchange frustration 16,50,51 , which suggests that HOI act in a similar way. The energy decomposition shows that the DMI contribution is of similar magnitude at the saddle point of the path with and without HOI (Fig.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In that respect, even at the saddle point, we confirm numerically that in soft ferromagnets a finite radius skyrmion solution exists as predicted in Ref. 27.…”
supporting
confidence: 87%
“…Recently, the saddle point configurations were explored theoretically, and it was found that even when the magnetic interactions are described in the continuum limit, a skyrmion of finite size could be expected as the saddle point configuration. 27 Here, we study the skyrmion collapse field B c of isolated skyrmions in Co islands of single atomic thickness on Ru(0001). In a previous work, 26 we have combined spin-polarized STM measurements and DFT calculations to explore the ground state properties of Co/Ru(0001) and showed that skyrmions were stabilized by a vanishing effective anisotropy in combination with a small DMI.…”
mentioning
confidence: 99%